Pentalinon andrieuxii Root Extract is Effective in the Topical Treatment of Cutaneous Leishmaniasis Caused by Leishmania mexicana. (8th November 2013) - Lezama‐Dávila, Claudio M.; Pan, Li; Isaac‐Márquez, Angelica P.; Terrazas, Cesar; Oghumu, Steve; Isaac‐Márquez, Ricardo; Pech‐Dzib, MY; Barbi, Joseph; Calomeni, Edward; Parinandi, Narasimham; Kinghorn, A. Douglas; Satoskar, Abhay R.
<x xml:space="preserve">Abstract</x> Cutaneous leishmaniasis (CL) manifests as localized skin lesions, which lead to significant tissue destruction and disfigurement. In the Yucatan Peninsula, Mayan traditional healers use Pentalinon andrieuxii Muell.‐Arg. (Apocynaceae) roots for the topical treatment of CL. Here, we studied the effect of P. andrieuxii root hexane extract (PARE) on the parasites and host cells in vitro and examined its efficacy in the topical treatment of CL caused by Leishmania mexicana. PARE exhibited potent antiparasitic activity in vitro against promastigotes as well as amastigotes residing in macrophages. Electron microscopy of PARE‐treated parasites revealed direct membrane damage. PARE also activated nuclear factor kappaB and enhanced interferon‐γ receptor and MHC class II expression and TNF‐α production in macrophages. In addition, PARE induced production of the Th1 promoting cytokine IL‐12 in dendritic cells as well as enhanced expression of the co‐stimulatory molecules CD40, CD80, and CD86. In vivo studies showed that L. mexicana‐infected mice treated by topical application of PARE resulted in the significant reduction in lesion size and parasite burden compared to controls. These findings indicate that PARE could be used as an alternative therapy for the topical treatment of CL. Copyright © 2013 John Wiley & Sons, Ltd.